Nationwide experience of catecholaminergic polymorphic ventricular tachycardia caused by RyR2 mutations. Issue 12 (25th February 2017) - Broendberg, Anders Krogh; Nielsen, Jens Cosedis; Bjerre, Jesper; Pedersen, Lisbeth Noerum; Kristensen, Jens; Henriksen, Finn Lund; Bundgaard, Henning; Jensen, Henrik Kjaerulf
Abstract : Objective: The aim of this study was to characterise disease penetrance, course of disease and use of antiarrhythmic medication and implantable cardioverter-defibrillator (ICD) therapy in a Danish nationwide cohort of patients with catecholaminergic polymorphic ventricular tachycardia (CPVT) due to mutations in the ryanodine receptor-2 ( RyR2 ) gene. Methods: The study population was identified through the national hereditary heart disease database (Progeny). The study population was divided into three groups: probands, symptomatic and asymptomatic relatives. Results: We identified 23 symptomatic probands, 18 symptomatic and 10 asymptomatic relatives with a RyR2 mutation. Twenty (87%) probands and 10 (36%) relatives had severe presenting symptoms (sudden cardiac death (SCD), aborted SCD (ASCD) or syncope). As compared with symptomatic relatives, probands had lower age at onset of symptoms (16 years (IQR, 10–33) vs 43 years (IQR, 25–54), p<0.0001) and were more prone to fatal or near-fatal events (ASCD, SCD) (16vs5, p<0.0001). Twenty-eight patients had an ICD implanted, and eight experienced appropriate ICD therapy during follow-up (65 months (IQR, 43–175)). Electrical storm was seen in two of the 28 ICD treated patients (7%). No patients receiving treatment died during follow-up (57 months (IQR, 32–139)). Multifocal atrial tachycardia was the predominant symptom in five patients. Conclusions: In a national cohort of RyR2 mutation-positive CPVT patients, SCD, ASCD and syncope were presenting events in the majority of probands and also occurred in 36% of relatives identified through family screening. Probands were younger at disease onset and more prone to fatal or near-fatal events than relatives.